BUILDING OPENING MODIFICATIONS AFFECTING WIND SPEED AT PEDESTRIAN LEVEL - Nazim N.M.; Hanipah M.H.; Zakaria M.A.; Jusoh W.A.W.; Yunus R.; Osman M.H.; Rahman M.F.A.; Jeni M.L.A.; Yazid M.N.A.W.M.; Ramli M.Z. (Construction Research Institute of Malaysia, 2024)
High land costs and shortage of accessible urban areas are some of the leading causes for the construction of highly dense high-rise structures. As a result, undesired low wind speeds that are generated due to excessive shielding contribute to heat stress issue. Recent studies have investigated the impacts of building opening in both subtropical and tropical climate zones as a popular architectural element to yield adequate ventilation around buildings. Nevertheless, only a handful of studies have examined building opening in any systematic way especially on wind speed at pedestrian-level for multiple buildings area. As such, this study assessed the effect of different building opening heights (BOHs) on pedestrian-level wind speed at multiple buildings area. The mean value for wind velocity ratio (MVR) was calculated by using data obtained from computational fluid dynamics (CFD) simulation. The study outcomes revealed that the optimum opening height at a range of 42%-64% generated the highest MVR = 0.39. In addition, the building opening elevation above than 86% of average building height has no longer affect the pedestrian level wind speed. In conclusion, the study findings provide evidence that optimum building opening design can effectively increase the mean value of wind speed at pedestrian level. 2023, Construction Research Institute of Malaysia. All rights reserved.